COVID – 19: A Critical Ontology of the present1. Issue 1 (2nd January 2021) - El Maarouf, Moulay Driss; Belghazi, Taieb; El Maarouf, Farouk
Abstract: COVID-19 has crowned 1 a number of other disasters (wildfires in Australia, Desert Locusts in Kenya, an imminent WWIII merging Iran and the US), causing panic to click into place and horror to become our global predicament, making us realize that we live in the illusion of the permanence of things, of mastery, and of immortality. People's turning to social media for trans-local news on COVID-19 has stirred great ire in the world. This led to the proliferation of dark images that associate the viral catastrophe with the end as we know it. To problematize the idea of the apocalypse (or the end) this paper speaks of three moments of survival in human existence: the beneath, the behind and the beyond. We argue that the apocalyptic nature of the pandemic and its global horrorism are part of a congeries of apocalyptic simulations that have always been part of the narrative with which we try to define ourexistence on earth. This paper masks itself against perfunctory examinations of the term apocalypse, and offers instead an understanding that runs along the lines of its Greek etymological sense as apokalyptein (revelation). It offers what Foucault calls an ontology of the present, that interrogates the history of COVID -19 with an emphasis neither on its origin nor on its telos. As beyondists, the COVID-19 catastrophe has revealed to us that 1) we have 'access to knowledge beyond knowledge' (see Gumpert 2012 ), and therefore that 2) our modern predicament is not very modern. The end, (not) to be sure, has been lived and relived in the boundary between reality and simulation. After all, the end of something comprises the beginning (in reverse) of that which "endeth", throwing the beyond, behind and beneath in the Ferris wheel of epistemological and existential entanglement.